GANDHES LUWES PROGRAM IMPLEMENTATION AS STRENGTHENING CHARACTER EDUCATION DURING THE COVID-19 PANDEMIC - Arif Surya Volta; Daffa Fakhri Maulana; Octavia Wulandari; Annisa Istiqomah (Universitas Tidar, 2023)
Gandhes Luwes become the flagship program of the Yogyakarta City Government to implement special values in everyday life through arts and culture, design, architecture and character attitudes of Yogyakarta. Within the education unit environment, this program is used as a medium for instilling character values in students. But during the Covid-19 pandemic the implementation gandhes luwes experience difficulty. There is one school that has run the program creatively amidst the limitations during the pandemic, namely SMPN 15 Yogyakarta. This study aims to determine the implementation of the program gandhes luwes at SMPN 15 Yogyakarta during the Covid-19 pandemic. The method used involves the principal, vice principal, teachers and students as resource persons in the interview. The data obtained was analyzed through the stages of data reduction, data presentation, then drawing conclusions that are described in accordance with the facts in the field. The findings show that program implementation gandhes luwes integrated into intracurricular and extracurricular activities in schools accompanied by the habituation of the special values of Yogyakarta. With this research, it is hoped that SMPN 15 Yogyakarta can become role model for other schools in implementing character education through gandhes luwes.